Efficient nickel-catalyzed phosphinylation of C–S bonds forming C–P bonds. Issue 82 (27th September 2016) - Yang, Jia; Xiao, Jing; Chen, Tieqiao; Yin, Shuang-Feng; Han, Li-Biao
Abstract : The first nickel-catalyzed phosphinylation of C–S bonds forming C–P bonds is developed. The reaction can proceed readily with the simple Ni(cod)2 at a loading down to 0.1 mol% at the 10 mmol scale. Various aryl sulfur compounds, i.e. sulfides, sulfoxides and sulfones all couple with P(O)–H compounds to produce the corresponding organophosphorus compounds, which provides an efficient new method for the construction of C–P bonds. Abstract : The first nickel-catalyzed phosphinylation of C–S bonds forming C–P bonds is developed. This transformation can proceed readily with the simple Ni(cod)2 at a loading down to 0.1 mol% at the 10 mmol scale. A variety of aryl sulfur compounds, i.e. sulfides, sulfoxides and sulfones all couple with P(O)–H compounds to produce the corresponding organophosphorus compounds in high yields, which provides an efficient new method for the construction of C–P bonds.